Validation of Goal Setting, Decision-Making Skills and Learning Satisfaction Scale Among Distance and Conventional University Learners in Nigeria - Ibrahim, Aminu Kazeem (West African Journal of Open and Flexible Learning, 2015)
The researcher modified a 13-item scale to measure goals setting, decision-making skills and learning satisfaction among distance and conventional university learners in Nigeria. The scale was initially developed by Mind tools, a website developer for general measurement. The validation sample was 187 males and 171 females. Exploratory factor analysis indicated that the scale measures four distinct dimensions: decision-making skills (DMS), goal setting skills (GSS), formulating learning goals (FLG) and learning satisfaction (LS). The sub-scale is brief (3 to 4 items each) and demonstrate good psychometric properties. Cronbach's alpha ranged from .79 to .90 across the four subscales. Criterion-related validity was demonstrated for each subscale. DMS was higher for distance university learners than conventional university learners; GSS was higher among distance university learners than conventional university learners; FLG was higher also among distance university learners than conventional university learners and LS was higher among conventional university learners than distance university learners. The scale was developed to support goal setting, decision-making skills and learning satisfaction among undergraduate university learners and it is potentially useful for both distance and conventional university learners.
Keywords: Goal setting; decision-making skills; learning satisfaction; distance and conventional leaders